Wider Economic Benefits of Transport Corridors : Evidence from International Development Organizations - Alam, Muneeza; Herrera Dappe, Matias; Melecky, Martin; Goldblatt, Ran (World Bank, Washington, DC, 2019)
This paper collects meta data on transport corridor projects financed by the Asian Development Bank, Japan International Cooperation Agency, and World Bank and links them to one important wider economic benefit -- local economic activity. The meta data cover 47 projects in 16 countries, with appraisal dates between 1991 and 2007. First, the paper reviews the variation in project design and implementation -- including the local initial conditions, complementary non-transport interventions, and private sector involvement. Second, using the difference-in-differences methodology, the paper links this variation to a measure of local economic activity -- the geocoded intensity of nighttime lights. The effect of the supported corridor projects on local economic activity could be very heterogenous and significantly depend on certain initial conditions and project characteristics. The latter could include locations with access to the sea, as well as projects with a strong theory of change and better engagement of the private sector.